Social-Cognitive Predictors of Readiness to Use Evidence-Based Practice: A Survey of Community-Based Rehabilitation Practitioners. (October 2016) - Pfaller, Joseph S.; Tu, Wei-Mo; Morrison, Blaise; Chan, Fong; Owens, Laura; Anderson, Catherine A.; Fitzgerald, Sandra; Brooks, Jessica; Menz, Fredrick E.
Community-based rehabilitation organizations (CBRO) play an important role in providing rehabilitation and support services to individuals with disabilities. Increased utilization of CBROs by state vocational rehabilitation (VR) agencies requires a better understanding of how evidence-based practices (EBPs) are used in CBROs. The aim of the study was to examine the readiness of CBRO practitioners to implement EBP, based on social-cognitive predictors of confidence in knowledge and use of EBP, expected benefits of EBP, and perceived barriers and supports to use EBP. A total of 187 CBRO practitioners were surveyed using the Evidence-Based Practice CBRO (EBP-CBRO) survey. Participants were in moderate agreement that they were ready to implement EBP. They were moderately confident in their knowledge about EBP, in high agreement about the expected improvements by using EBP, and perceived low barriers and moderate supports to implementing EBP. The social-cognitive predictors accounted for 55% of the variance in readiness to implement EBP, with knowledge about EBP as the most significant predictor of readiness to use EBP. Social-cognitive theory is a useful framework for exploring CBRO practitioners' attitudes toward and knowledge of EBP. CBRO practitioners are in moderate agreement about readiness to use EBP. Improving practitioner confidence to use EBP might be the best means of increasing utilization.